Knowledge and Awareness of Medical and Dental Students About Oral Cancer Risk Factors: A Systematic Review and Meta-Analysis - Lilibeth-Stephania Escoto-Vasquez MSc; Mario Alberto Alarcón-Sánchez MSc; Ruth Rodríguez-Montaño PhD; Julieta Sarai Becerra-Ruiz PhD; Sarah Monserrat Lomelí-Martínez PhD; Artak Heboyan PhD (Cancer Control)
Objective This systematic review and meta-analysis aims to assess the knowledge and awareness of oral cancer risk factors among medical and dental students. Methods This study followed the PRISMA guidelines and was registered in INPLASY (ID: 2024110035). Four databases were consulted (PubMed, Science Direct, Scopus, and Web of Science) from February 20th, 2005, to May 10th, 2024. The study selection and data extraction process was performed independently by 2 investigators. The risk of bias was assessed using the JBI tool, which can be found at: https://jbi.global/critical-appraisal-tools . A third investigator was consulted in case of disagreement. Meta-analysis results were systematically illustrated in a forest plot and expressed as odds ratio with 95% confidence interval. The I 2 statistic assessed heterogeneity between studies. Funnel plot and Egger regression analysis were used for bias analysis. A P value <.05 was considered significant. All statistical analyses were performed using the STATA V.15 software. Results After the selection process, 41 studies met the eligibility criteria, comprising a total of 14,425 participants, 22% medical students and 78% dental students, primarily female (53%). The meta-analysis showed that 98% of students demonstrated relatively good knowledge about oral cancer risk factors. The most recognized risk factor was smoking (99%), followed by advanced age (68%), UV-rays exposure (64%), and alcoholism (57%). Knowledge of several other factors was comparatively lower, with less than 50% of students recognizing them. The studies indicated significant heterogeneity (I 2 = 99.8%) and publication bias ( P < .001). Conclusions These findings suggest that while medical and dental students have a strong understanding of key risk factors for oral cancer, there are gaps in knowledge regarding other important factors. Addressing these gaps through enhanced education and training is essential to improving early detection and prevention efforts.